"The Fall of the House of Flint": A Zooarchaeological Perspective on the Decline of Chipped Stone Tools for Butchering Animals in the Bronze and Iron Ages of the Southern Levant. (November 2013) - Greenfield, Haskel J.
Abstract : In recent years, it has been recognized that chipped stone tools continue to be used after the end of the Neolithic in spite of the introduction of metallurgy. However, the rate of change from a lithic to metal-based economy is affected by the type of tool and its various functions. Traditionally, this change is monitored through the frequencies and presence/absence of the various lithic tool types. These data are often negatively affected by the haphazardly collected lithic collections from Bronze and later sites. Recently, an alternative approach to monitoring the shift in technology has been proposed. Microscopic examination of butchering marks on animal bones allows the type of raw material (stone versus metal) and the type of implement (blade versus scraper) to be reconstructed. In this paper, zooarchaeological data from the southern Levant (Israel and Palestinian Authority Territory) will be used to demonstrate the nature and rate of change from a stone to a metal-based animal butchering technology during the Bronze Age. The data demonstrate that chipped stone tools use continues to be widespread during the Early Bronze Age at both urban and rural sites for the butchering of animal remains and tool making. From the beginning of the Middle Bronze Age (II), there is a dramatic shift in emphasis to a metal-based technology (ca. 80 percent) corresponding with the spread of high quality tin-bronze metal knives. In the Late Bronze Age, the frequency of chipped stone tools continues to decline. The transition from stone to a metal-based butchering technology is almost complete by the Iron Age, but chipped stone tools never fully disappear in the butchering process even in subsequent periods. Chipped stone tools continue in use long after the end of the Neolithic.